2001
DOI: 10.1038/sj.cgt.7700288
|View full text |Cite
|
Sign up to set email alerts
|

Effective infection, apoptotic cell killing and gene transfer of human hepatoma cells but not primary hepatocytes by parvovirus H1 and derived vectors

Abstract: Autonomous parvoviruses preferentially replicate in and kill in vitro ± transformed cells and reduce the incidence of spontaneous and implanted tumors in animals. Because of these natural oncotropic and oncolytic properties, parvoviruses deserve to be considered as potential antitumor vectors. Here, we assessed whether parvovirus H1 is able to kill human hepatoma cells by induction of apoptosis but spares primary human liver cells, and whether the former cells can efficiently be transduced by H1 virus ± based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
99
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(107 citation statements)
references
References 21 publications
7
99
1
Order By: Relevance
“…These results were confirmed by Northern blot analysis (Figure 1a). To determine whether Noxa mRNA induction was restricted to SV infection and/or dependent on p53 activation, experiments were carried out using HSV-1, a DNA virus and HuH7 cells, which contain a functionally inactive p53 gene (Moehler et al, 2001). As shown in Figure 1a, both SV and HSV-1 infection markedly induced expression of NOXA transcripts in both p53 positive and negative cell lines.…”
Section: Noxa Is Induced During Virus Infectionmentioning
confidence: 99%
“…These results were confirmed by Northern blot analysis (Figure 1a). To determine whether Noxa mRNA induction was restricted to SV infection and/or dependent on p53 activation, experiments were carried out using HSV-1, a DNA virus and HuH7 cells, which contain a functionally inactive p53 gene (Moehler et al, 2001). As shown in Figure 1a, both SV and HSV-1 infection markedly induced expression of NOXA transcripts in both p53 positive and negative cell lines.…”
Section: Noxa Is Induced During Virus Infectionmentioning
confidence: 99%
“…35 Previous analyses have demonstrated that H-1PV was able to induce specific immune responses against the tumor and TCLs. 4 Therefore, autonomous parvoviruses offer a new approach in the treatment of cancer, although the susceptibility of the tumor cells to H-1PV infection is dependent on the origin of the tumor and the proliferation capacity of the cells. 36 Based on previous studies which analyzed TLR-2, -3, -4, -6 and -9 -transfected HEK293 cells (data not shown), only a TLR3-and TLR9-mediated activation of NFkB could be detected after H-1PV infection.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 One special characteristic of these rodent viruses is their absence of pathogenicity in adult animals and if any, is restricted to proliferating tissues and to fetuses or neonates. 3 H-1PV is considered oncotropic, efficiently infecting transformed human cell lines and human tumor cells, including melanoma, hepatoma, colon and gastric cancer cells [4][5][6] ; however, in contrast to these fast replicating cells, human immune cells and primary hepatocytes are not infected or lysed. 4,5,7 It was reported that H-1PV can also replicate in humans after injection without causing severe adverse reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Oncolytic viral therapy (OVT) utilizes the selective replication of viruses in cancer cells to lyse tumor cells and release tumor antigens, while leaving normal tissue unaffected. 3,4 OVT represents an emerging therapeutic modality that has achieved tumor regression in clinical trials.…”
Section: Introductionmentioning
confidence: 99%